2016
DOI: 10.1016/j.ijscr.2016.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy in a 2 year old male child with choleilithiasis and recurrent right hypochondrial pain: Case report and review of literature

Abstract: HighlightsThe probability of gallstone disease infants and young children should not be ignored.Gall stones should always be considered as a differential diagnosis when young patients present with complaints of abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Laparoscopic cholecystectomy is considered to be a gold standard procedure for gallbladder removal (Chhabra et al, 2016). Indeed, millions of people have undergone this type of surgery annually.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic cholecystectomy is considered to be a gold standard procedure for gallbladder removal (Chhabra et al, 2016). Indeed, millions of people have undergone this type of surgery annually.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this type of plant could be applied as a pharmacologic compound in the healthcare setting and specifically utilized in treating neurologic diseases (Ozgoli et al, 2013). Several studies have evaluated aromatherapy with Lavandula angustifolia Miller extract as a non-invasive nursing intervention in different settings, such as anxiety improvement of patients who have undergone angiography and stenting, hemodialysis, dentistry and/or general surgeries, and decreasing cortisol concentration and cardiac parameters, including blood pressure and pulse rate (Chhabra et al, 2016). Other studies indicated insignificant effects of aromatherapy on preoperative anxiety in patients undergoing different types of surgery and those undergoing radiotherapy (Pimenta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Diseases of the biliary system are closely related to violations of the functional state of the liver. Synthesis of cholesterol supplemented bile with reduced bile acid content significantly increases the risk of gallstones, as well as gallbladder cholesterol (Özkardeş et al, 2014;Coats et al, 2015;Tsai et al, 2015;Chhabra et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The study doesn't classify patients according its severity, i.e. Acute Cholecystitis grade I, II or III according to Tokyo guidelines, therefore we cannot tell whether the treatment was early, late or in between, which may affect mortality.It is referred that there was a major expense on children under 4 years coursed with cholelithiasis or cholecystitis, probably due to the oddness of thinking of cholelithiasis as a diagnosis in this group and it also requires further studies and a more complex treatment than adults 4 . …”
mentioning
confidence: 98%
“…It is referred that there was a major expense on children under 4 years coursed with cholelithiasis or cholecystitis, probably due to the oddness of thinking of cholelithiasis as a diagnosis in this group and it also requires further studies and a more complex treatment than adults 4 .…”
mentioning
confidence: 99%